SPECIFIC CHARACTERISTICS OF THE LAW ON THE PREVENTION OF DOMESTIC VIOLENCE - Stevanović, Obrad; Subošić, Dane; Kekić, Dalibor (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Abstract: The current Law on the Prevention of Domestic Violence basically regulates the organization, goals and manner of acting of competent state authorities and institutions in preventing this type of violence and in protecting victims and supporting victims of this violence in the Republic of Serbia. Experiences of competent police officers, prosecutors and judges acquired during their specialized training and nine-month practical implementation of the Law on Prevention of Domestic Violence, confirmed some of the specific characteristics, but also pointed out some problems in the implementation of the Law. Starting from this, the research whose results were presented in the work was aimed at identifying, systematizing and scientifically describing the characteristics of the Law on the Prevention of Domestic Violence that are of particular importance for understanding its essence and for its effective and efficient implementation. The results of such directed research, as particularly important characteristics of this Law, have been identified in the paper as well: 1) targeted the Law on preventive action (prevention) and higher level of expertise of officials for the application of protection of victims of violence (protection), 2) formalization of the risk assessment procedure and pronouncement of urgent measures (processing), 3) the statutory law (competence) cooperation and coordination of activities between competent authorities and institutions in its implementation (integration). Such a conception of legal solutions, conditions have been created to overcome some of the previously expressed problems of preventing domestic violence. Најзначајнији од њих су: The most significant of these are: 1) the problem of "dark figures" as a consequence of the absence of reporting and processing of domestic violence, 2) the problem of legal and security vacuum in the protection of victims, 3) the problem of insufficient competence and the lack of cooperation between providers of prevention of domestic violence and 4) the problem of overlap and / or gap in the structure of responsibility for the protection of victims of this violence.